KEPASTIAN HUKUM SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN TANPA PENERBITAN AKTA PEMBERIAN HAK TANGGUNGAN PADA KPR BERSUBSIDI - Vania Carissa Salsabila (2023)
Indonesia is the fourth most populous country in the world. This has an impact on the large demand for decent housing for the people of Indonesia. However, the amount of demand is inversely proportional to the people's purchasing power which tends to be low, in this case the government and also banks as credit institutions play an important role in overcoming this problem. Subsidized mortgages are considered the answer for low-income people to own housing. Subsidized KPR collateral objects are often only tied to SKMHT without APHT as a result of the lengthy process of splitting land certificates. In this study the authors raise the topic of the validity of the mortgage itself with the aim of analyzing legal certainty rather than SKMHT issued without APHT. In this study, the method that the author uses is normative juridical by using a statutory approach. The legal material analyzed is Law no. 4 of 1996 concerning Mortgage and Minister of Agrarian Regulation No. 22 of 2017. The results of this study explain that by not registering mortgage rights, the bank as a creditor is only a concurrent creditor. Banks are considered to have no factually guaranteed material rights and it is necessary to increase SKMHT to APHT so that it can provide certainty and binding legal protection for the parties in the event of default.